QUANTITATIVE ASSESSMENT OF COASTAL RESPONSE AT POINT PELEE ON LAKE ERIE 1974-75 - Shaw, John (My University, 1977)
The concern about the preservation of a valuable natural resource such as Point Pelee is readily apparent, yet along with this concern is the need for raw materials such as aggregates dredged from submarine sand and gravel deposits. This could involve a conflict in resource management, therefore the question of how significant commercial dredging is as a process element in the local coastal dynamics needs to be resolved. To provide a basis for this assessment, offshore and onshore surveys, bottom sediment analyses, wind-wave analyses, and current measurements have bee·n taken over the last two years to derive a sediment budget for the Point Pelee spit and shoal system.
The magnitude of response was measured by the morphologic and volumetric variation between successive profiles at 18 sites throughout Point Pelee. The beach zone of the east shore evidenced the most dramatic morphologic and volumetric changes to its profile, with an average loss of 17.5 m3/m from fall to spring of 1975.
Maximum material restored to the east beach in 197-5 was 4.5 m3/m. In terms of annual.quantitative changes to the beach budget, the westward migration of the Point is five times greater for the east shore than for the west. The sediment budget for 1974-75 shows a net deposition to the south of Point Pelee on the order of 440,000 m3.
Keywords: coastal response; point pelee; sand deposits; coastal process; preservation